for the longest while i've been working on this question

can any 1 help me out here

Code:

f(x) = 3^(x + 1) and g(x) = 3-x + 3 .

Find the point of intersection of the graphs of f and g by solving f(x) = g(x).

Printable View

- Nov 18th 2010, 08:01 AMmath321graphing question
for the longest while i've been working on this question

can any 1 help me out here

Code:

f(x) = 3^(x + 1) and g(x) = 3-x + 3 .

Find the point of intersection of the graphs of f and g by solving f(x) = g(x).

- Nov 18th 2010, 09:07 AMUnknown008

Is that it? g(x) seems strange... - Nov 18th 2010, 09:14 AMmath321
sorry this is what the question said

Code:`3^{x+1} = 3^{-x+3}`

- Nov 18th 2010, 09:16 AMUnknown008

Insert log on both sides:

Can you finish now? (Smile) - Nov 18th 2010, 09:21 AMmath321
so am i solving for x

using quadratic

then what - Nov 18th 2010, 09:22 AMUnknown008
You don't need to use quadratic... (Wondering)

- Nov 18th 2010, 09:25 AMmath321
so how am i going to get the points

- Nov 18th 2010, 09:26 AMUnknown008
You solve for x...

- Nov 18th 2010, 09:29 AMmath321
3-x -x -1=0

-2x +2 = 0

x = -1

is it this

what do i do after - Nov 18th 2010, 09:31 AMUnknown008
Since you are looking for the point of intersection, you are looking for a coordinate.

You already have the x coordinate, what can you do it this and the two equations:

- Nov 18th 2010, 09:34 AMmath321
so i solved the equation above and got -1

so am i going to substitute it in fx and gx

and solve - Nov 18th 2010, 09:40 AMUnknown008
Yes (Smile)

Substituting in either f(x) or g(x) should be enough though. - Nov 18th 2010, 09:52 AMmath321
i guess i have to substitute for both

bcuz they said for f and g

for f i got (-1,1)

any suggestions - Nov 18th 2010, 09:59 AMUnknown008
Well... actually you didn't solve for x properly... I thought that you were doing the calculations well, but a small mistake crept in:

-2x +2 = 0

-2x = -2

x = 1

Now, find your y coordinates. - Nov 18th 2010, 10:27 AMmath321
cud u jus verify this for me

0 = 3-1-2x

0 = 2-2x

-2= -2x

x=1

f(x) = 3^(x+1)

f(x) = 3^ (1+1)

f(x)= 9

g(x) = 3^(-1+3)

g(x) = 3^(2)

g(x) = 9